Spodoptera frugiperda: Hama utama pada tanaman jagung dan strategi pengendaliannya - Anintyas, Dytri; Safitri, Khofifah Nur Indah; Kusumawati, Eka; Masoyogie, Kholfira; Dirmawati, Suskandini Ratih; Aeny, Titik Nur; Suharjo, Radix (Jurnal Proteksi Agrikultura, 2024)
Spodoptera frugiperda (FAW), or fall armyworm, is a major invasive pest that attacks corn crops in various tropical and subtropical regions. In recent decades, the global spread of FAW has been accelerated by international trade and climate change. In Indonesia, the presence of this pest was first reported in 2019 in West Sumatra, with attacks spreading to various other areas. The FAW life cycle includes four stages (eggs, larvae, pupae, and imago) with significant levels of plant damage, especially in the larval stage.Various con- trol strategies have been implemented, including integrated pest management (IPM) approaches, such as the use of biological agents (Beauveria bassiana and Metarhizium anisopliae), push-pull techniques, and crop rotation. In addition, the development of pest-resistant corn varieties is an important alternative. Recent re- search has identified two genetic lines of FAW, namely corn and rice lines, which show differences in host preference and resistance to insecticides.This study highlights the need for further development of ecologi- cally based strategies, including exploration of local parasitoids and effective bioinsecticide formulations. In addition, genetic and microbiota analyses offer new potential in understanding FAW population dynamics and its control. These results are expected to be the basis for sustainable pest management in Indonesia and other regions.